Pengalaman Keluarga dalam Pemenuhan Kebutuhan Perawatan Diri pada Orang Dengan Gangguan Jiwa (ODGJ) dengan Pasung di Kecamatan Ambulu Kabupaten Jember (The Family Experience in Fulfilling the Needs of the Self-care of People with Chronic Mental Health Ill - nuriyah halida; Erti Ikhtiarini Dewi; Hanny Rasni (UPT Percetakan dan Penerbitan Universitas Jember, 2016)
Every problem of psychiatric nursing that may occur in seclusion of people with chronic mental health illness (ODGJ) is self-care. Self-care is one of the basic human abilities to meet his needs in order to survive, be healthy and be prosperous in accordance with the health condition. Family is an important part in motivating during the care and in treatment of ODGJ. This research aimed to describe the family experience in meeting the need of self-care in ODGJ by seclusion. The research used qualitative design with phenomenological study approach. The sampling technique used purposive sampling and snowball sampling. This research experienced a data saturation in the sixth participant, so the number of participants in this research was 6 people. The results found 12 research themes, that is, the fulfillments of self-care in: eating, air, bathing, hair cutting, dressing, defecation, rest and sleep, drinking and social interaction, inability to fulfill the task of development ODGJ, the implementation of seclusion on ODGJ and therapy for ODGJ. The need of ODGJ’s self-care by seclusion can be met by active role of family, community and health services for treatment. Keywords: family, self-care treatment, people with chronic mental health illness (ODGJ) with seclusion